Abnormal levels of vascular endothelial biomarkers in schizophrenia - Nguyen, Tanya T.; Dev, Sheena I.; Chen, Guanqing; Liou, Sharon C.; Martin, Averria Sirkin; Irwin, Michael R.; Carroll, Judith E.; Tu, Xin; Jeste, Dilip V.; Eyler, Lisa T. (European archives of psychiatry and clinical neuroscience, 2018)
Schizophrenia is associated with chronic low-grade inflammation, which has been linked to increased vascular risk and rates of cardiovascular disease. Levels of vascular endothelial growth factor (VEGF), intercellular adhesion molecule-1 (ICAM-1), and vascular cell adhesion molecule-1 (VCAM-1) have been related to aging and neurodegeneration, but their role in schizophrenia remains uncertain. Using a cross-sectional, case–control design, this study included 99 outpatients with schizophrenia and 99 healthy comparison subjects (HCs). Sociodemographic and clinical data were collected, and plasma levels of VEGF, ICAM-1, and VCAM-1 were assayed. A “vascular endothelial index” (VEI) was computed using logistic regression to create a composite measure that maximally differed between groups. General linear models were conducted to examine the possible role of demographic, physical, and lifestyle factors. A linear combination of ICAM-1 and VCAM-1 levels best distinguished the groups, with significantly higher levels of this composite VEI in persons with schizophrenia than HCs. Group differences in the VEI persisted after adjustment for BMI and cigarette smoking. Neither age nor gender was significantly related to the VEI. Schizophrenia patients with higher VEI had earlier age of disease onset, higher systolic and diastolic blood pressure, lower high-density lipoprotein cholesterol, higher insulin resistance, lower levels of mental well-being, and higher Framingham Coronary Heart Disease Risk scores. Schizophrenia is characterized by an elevation of vascular endothelial biomarkers, specifically cell adhesion molecules poised at the intersection between inflammatory response and vascular risk. Interventions aimed at reducing vascular risk may help reduce vascular endothelial abnormalities and prevent cardiovascular morbidity and mortality in schizophrenia.